(untitled) (Homoeopathy for All, 2024)
Dr. S.P.S. Bakshi imbibed many qualities from his father, Dr. Kirpal Singh Bakshi, who was not only a legend in the field of homoeopathy but also a pioneering figure in popularizing this alternative medical science in India. Honorary physician to the then Hon ’ ble President of India, Giani Zail Singh, Dr. K.S. Bakshi went on to receive the prestigio us Hahnemann International Award. He has to his credit, es tablishment of the first ever homoeopathic clinic at the Rashtrapati Bhawan complex. His effort s and the results, which we are witnessing now, have been phenomenal.Call it curiosity or a will for greater good, that in 1947, Dr. K.S. Bakshi, at the age of 32, gave up a lucrative career in the Indian Army and decided to pursue homoeopathy. The zeal was answered; the man was conferred with a gold medal from the Calcutta Homoeopathic College at the culmination of his studies in 1952. In 1965, he started teaching Homoeopathic Materia Medica at the Nehru Homoeopathic Medical College. It wasn’t a mere coincidence that Dr. K. S.